2022
DOI: 10.1111/jace.18862
|View full text |Cite
|
Sign up to set email alerts
|

MSO4 (M = Ca, Sr, Ba) microwave dielectric ceramics with low dielectric constant

Abstract: MSO 4 (M = Ca, Sr, Ba) ceramics with relative densities exceeding 96% were prepared by solid-state sintering at low sintering temperatures of 625-875 • C, and their structures and microwave dielectric properties at 10-19 GHz were characterized. MSO 4 ceramics crystallized in orthorhombic symmetry with the space groups of Amma for CaSO 4 and Pnma for SrSO 4 and BaSO 4 . The optimal microwave dielectric properties were obtained with ε r = 5.85, Qf = 57 000 GHz, τ f,W = −98.8 ppm/ • C for CaSO 4 , ε r = 10.95, Qf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Meanwhile, τ f of microwave dielectric ceramics is usually regarded as a constant independent of temperature over a wide temperature range, whereas in reality τ f strongly depends on temperature and even changes positively or negatively with temperature. Therefore, measuring the resonant frequency at two temperature points only for τ f may lead to errors in the true temperature stability of microwave dielectric ceramics, thus seriously misleading their practical applications 3,4,40 . So it is necessary to study τ f in two or more temperature ranges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, τ f of microwave dielectric ceramics is usually regarded as a constant independent of temperature over a wide temperature range, whereas in reality τ f strongly depends on temperature and even changes positively or negatively with temperature. Therefore, measuring the resonant frequency at two temperature points only for τ f may lead to errors in the true temperature stability of microwave dielectric ceramics, thus seriously misleading their practical applications 3,4,40 . So it is necessary to study τ f in two or more temperature ranges.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, measuring the resonant frequency at two temperature points only for τ f may lead to errors in the true temperature stability of microwave dielectric ceramics, thus seriously misleading their practical applications. 3,4,40 So it is necessary to study τ f in two or more temperature ranges. Existing work has confirmed the feasibility of this approach, 8,25,41-…”
Section: Resultsmentioning
confidence: 99%
“…14 Therefore, it is still desired to have LTCC materials with high-CTE and excellent dielectric properties for highly reliable packages. Li et al 15 reported that BaSO 4 ceramics had low-ε r , near-zero temperature coefficient of resonant frequency (TCF) and a low sintering temperature of 875 °C. However, there are some differences with regard to our work on BaSO 4 ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…As the key materials for resonators and filters, microwave dielectric ceramics are required to possess an appropriate dielectric constant ε r to balance smaller device size and working frequency, high-quality factor Q to obtain excellent frequency selectivity and near-zero temperature coefficient of resonant frequency τ f to ensure the temperature stability. [1][2][3] Although a number of microwave dielectric ceramics have been developed, [4][5][6] pursuing the optimum combination of these three parameters is still a big challenge. Generally, tuning and improving the Q value and τ f are considered to be the crucial task for obtaining the microwave dielectric ceramics with a specific ε r .…”
Section: Introductionmentioning
confidence: 99%